Plasma Technology for CO2 Conversion: A Personal Perspective on Prospects and Gaps - Bogaerts, Annemie; Centi, Gabriele (Frontiers in energy research, 2020)
There is increasing interest in plasma technology for CO2 conversion because it can operate at mild conditions and it can store fluctuating renewable electricity into value-added compounds and renewable fuels. This perspective paper aims to provide a view on the future for non-specialists who want to understand the role of plasma technology in the new scenario for sustainable and low-carbon energy and chemistry. Thus, it is prepared to give a personal view on future opportunities and challenges. First, we introduce the current state-of-the-art and the potential of plasma-based CO2 conversion. Subsequently, we discuss the challenges to overcome the current limitations and to apply plasma technology on a large scale. The final section discusses the general context and the potential benefits of plasma-based CO2 conversion for our life and the impact on climate change. It also includes a brief analysis on the future scenario for energy and chemical production, and how plasma technology may realize new paths for CO2 utilization.